A Better Choice for Primary Anterior Tooth Restoration Between Strip Crowns and Zirconia Crowns: A Narrative Review - Karuna YM; Ramya Shenoy; Ashwin Rao; Shweta Rao; Anupama Nayak P (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pediatric dentists very commonly encounter patients with carious primary maxillary anterior teethdemanding esthetic treatment. Meeting this need of the patient and their parents is the greatest challengeto the clinician, considering the tender age of the patient and limited cooperation available during thetreatment. Strip crowns were popularly used conventional esthetic restorative option to treat such teethwith a good degree of acceptance from patients and their parents. However, they are technique sensitiveand have other disadvantages. The process of overcoming these drawbacks introduced zirconia crowns tothe primary anterior esthetic armamentarium. This review discusses the comparison between strip crownsand zirconia crowns for primary anterior tooth restoration. The PubMed database was accessed to search forrelevant articles using key terms: (primary anterior teeth) AND (strip crown) and (primary anterior teeth)AND (zirconia crowns).